A silica sands-based method for faithful analysis of microbial communities and DNA isolation from a wide range of species. Issue 4 (21st April 2018) - Liu, Xia; Xu, Yongdong; Li, Zhi; Jiang, Shengwei; Yao, Shuo; Wu, Rina; An, Yingfeng
ABSTRACT: A silica sands-based method has been developed to isolate high quality genomic DNAs from cells of animals, plants and microorganisms, such as Hemisalanx prognathus, Spinacia oleracea, Pichia pastoris, Bacillus licheniformis and Escherichia coli . To the best of our knowledge, no DNA isolation method has so wide application until now. In addition, this method and a commercially available kit were compared in analysis of microbial communities using high-throughput 16s rDNA sequencing. As a result, the silica sands-based method was found to be even more efficient in isolating genomic DNA from gram-positive bacteria than the kit, indicating that it would become a very valuable choice to faithfully reflect the composition of microbial communities.